Desenhos e Gráficos: Produção de Significados Pelos Participantes de Um Curso de Geometria Analítica - Goulart, Jany Santos Souza (2008)
This investigation aims to analyze the way how students and professor, who study and teachers classes of analytic geometry, respectively, in a group of Mathematics Undergraduate students at the State University of Feira de Santana / BA, conceive aspects related acquisition, construction and interpretation of senses or meanings, produced or exposed in the classroom. To this, a research is carried out supported on the ethnographical practice from the proposal and argument that an environment is constituted in a multicultural cognitive universe or even in a microsociety, rich in production of meanings. This way, it is used observations in which the researcher places herself in a strangement position and quest for impartiality. In this context, it is admitted that graphical representations carry along psychological and sociological factors, perceptive, cognitive and affective specifics schemes or that social and cultural factors are directly related to multiple interpretations concerning a geometrical, mathematical and symbolical element. The experiences are brought, through the emphasis or selection of characteristic episodes of involved performers’ (professor-students) way of meaning. This investigation objective is to present answers as for drawings, graphics, pictures role or level of importance in the built meaningful inter-relationships. In equal dimension, it aims to understand the influences and individual conceptions reach in the social environment as well as to build a classroom operation prospect, taking in consideration the particular matters on the geometrical picture study, usually considered as carriers of ambiguities and implicit meanings. The combination between algebraic and graphic language and semiotic studies are presented in all study construction as a method to obtain valid solutions and description of meaning processes.